Hubungan Dukungan Keluarga Terhadap Kualitas Hidup Pasien Tuberkulosis Paru: Hubungan Dukungan Keluarga Terhadap Kualitas Hidup Pasien Tuberkulosis Paru - yusniawati, Yustina Ni Putu (JURNAL KESEHATAN PRIMER, 2021)
: Tuberculosis (TB) is a common disease in developing countries with the ratio of male and female patients are between 15 and 59 years old. Pulmonary TB disease is a contagious disease found in developing countries like Indonesia and usually occurs on children and adults. The problem is TB treatment include TB-HIV AIDS, OAT resistance, TB with metabolism, and TB children needs support from various aspect such as the government in controlling TB. Health practitioners should not only wait at the Public Health Centre but also take an action to search in the community. The purpose of this study was to identify the correlation between family supports to quality of life on patients with pulmonary TB in public health center south Denpasar and west Denpasar. This study employed observational analytical study with cross sectional approach. Family support questionnaire was modified from the Medical Outcomes Study (MOS) Social Support Survey (Sherbouren and Stewart, 1991) And life quality was modified from questioner WHOQOL-BREF (2004). Data collection is done by self-administered questionnaire. Univariate analysis was used to determine the demographic data of respondents, the majority of patients are male, with a diagnosis of Positive BTA, with a family type that is the nuclear family. Bivariate test was used spearmen rho to determine the correlation of family support to the quality of life on patients with pulmonary TB in Public Health Centre in South Denpasar and West Denpasar. The result showed that P 0,000 <a = 0.05 and r = 0.959 which meant there was significantly correlation between family support to quality of life on patients with TB in Public Health Centre in South Denpasar and West Denpasar The researcher suggested that health professionals, especially nurses, should be able to approach counselling to families of patients with pulmonary TB in order to motivate pulmonary TB patients to be obedient to taking medication and have a passion for recovery.